MERAJUT KEBERSAMAAN DI TANAH BERTUAH: INTEGRASI DAN PLURALISME DI KOTA KISARAN - Ramadhan, Nugraha Pratama; Dora, Nuriza; Amanda, Ahmad (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2025)
This research is to analyze in depth the forms of interaction and strategies of the Kisaran City community in maintaining integration and pluralism amidst the diversity of ethnicities, religions and cultures. This research employs a descriptive qualitative method with data collection techniques through in-depth interviews with various informants, including community leaders, Malay customary leaders and Islamic religious figures, Batak Christian customary leaders, and local residents. Data were collected using structured interview guidelines and analyzed thematically. The results show that harmonious life in Kisaran City is realized through social interactions based on mutual respect, joint implementation of traditions and celebrations, and the strengthening of local wisdom values such as mutual cooperation (gotong royong), deliberation (musyawarah), and mutual empathy (tepo seliro). The main challenges faced include the rapid flow of information in the globalization era, which has the potential to trigger misunderstandings, and the declining interest of the younger generation in local values. To address these issues, the community and government actively conduct socialization, strengthen communication forums, and involve the younger generation in various social and cultural activities. This study concludes that diversity in Kisaran City becomes a social strength that fosters solidarity and collective progress, provided that the values of tolerance and togetherness are continuously upheld.